Kinematics and Dynamics Analysis and Simulation of the NGW Type Differential Mechanism - Liu Ting; Cui Peijuan; Wang Chunming; Xiao Chong; Yue Zhenbo; Beijing Research Institute of Precise Mechatronic Controls Equipment (Jixie chuandong)
The kinematics and rigid- body dynamics theoretically analysis and the ADAMS simulations of the NGW type planet differential mechanism are carried out. The kinematics analysis show the results that the mechanism can realize the velocity synthesis and differential operation with different speed of two input shafts.Through the rigid- body dynamics analysis,the results as following. Firstly,the relations among the two input angular accelerations,two input torques,the interaction forces between the planet carrier and the planetary gear,the meshing forces at a tangent between gears in case of acceleration and deceleration are derived. Secondly,the relation between the two input axes angular accelerations and two input torques and one load torque is derived. Thirdly,the relation between load torque and the two input torques and two input axes angular accelerations is derived. Fourthly,the force amplitudes between the sun gear and its planetary gears are equal to each other. Fifthly,the force amplitudes between the internal gear ring and its planetary gears are equal to each other. Lastly,the interrelation relationships of the angular accelerations are matched with kinematics relationships.The simulation results by ADAMS are consistent with theoretical consequences. The theoretical analysis is proved to be correct. The results can be applied to performance analysis of the differential mechanism in redundant electromechanical servo actuation systems in case of acceleration and deceleration.